Some Local Properties of Soft Semi-Open Sets - Bin Chen (Discrete Dynamics in Nature and Society)
We introduce some local properties by soft semi-open sets. For example, soft semi-neighborhoods of the soft point, soft semi-first-countable spaces and soft semi-pu-continuous at the soft point are given. Furthermore, we define soft semi-connectedness and prove that a soft topological space is soft semiconnected if and only if both soft semi-open and soft semi-closed sets are only ∅ and X~.